Jejak Tarekat Tijaniyah Di Nusantara: Studi Tentang Perkembangan dan Adaptasi Lokal - Sirojuddin, Ahmad Sholihin; Alfanny, M. Saad; Kamal Yusuf (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The beginning of the Tijaniyah order appeared in the archipelago at the beginning of the 20th century between 1920 and 1928. This research aims to explore the traces of the emergence of this order in the archipelago. Despite the challenges, the order continued to grow in several areas, especially in Cirebon and Garut (West Java), Madura, and the eastern tip of Java Island. The purpose of this article is to find out when tarekat tijinyah began to exist in the archipelago and how it developed and adapted. This research also strengthens the analysis by comparing and examining other relevant sources. The data analysis method used is descriptive analysis, which describes in detail and in depth to obtain an accurate understanding. The result of this research shows that the internal development is done through intensive coaching in each region for Tarekat Tijaniyah students, giving muqaddam duty schedule to foster and provide recitation material in hailalah places in turn, and structuring the administration of Tarekat Tijaniyah. Meanwhile, the development of external relations was carried out by establishing cooperation with the government and socio-political organisations. The development of Tarekat Tijaniyah is strongly influenced by the important role of muqaddam (teachers) in spreading its teachings. In addition, the relatively easy teachings and requirements for Tijaniyah followers also facilitated its spread in the archipelago.